Water consumption and prevalence of irritable bowel syndrome among adults. - Asma Salari-Moghaddam; Ammar Hassanzadeh Keshteli; Ahmad Esmaillzadeh; Peyman Adibi (PLoS ONE, 2020)
BACKGROUND AND AIM:No previous study examined the association between whole-day water intake and odds of irritable bowel syndrome (IBS). We examined the association between whole-day water intake and odds of IBS in a large sample of Iranian adults. METHODS:This cross-sectional study was conducted among 4763 adults in Isfahan, Iran. Daily water intake was assessed using a pre-tested questionnaire by asking questions about the average number of glasses of water consumed in a day. IBS was assessed and defined using a modified Persian version of Rome III questionnaire. RESULTS:After taking potential confounders into account, no significant association between water consumption and odds of IBS was seen (OR: 1.14; 95% CI: 0.74-1.78). We observed that participants who were taking >8 glasses/d of water had greater odds of IBS-M in comparison to those who consumed <2 glasses daily (OR: 2.07; 95% CI: 1.01-4.22). No significant association was observed between water intake and odds of IBS in either gender as well [for men: OR: 1.15; 95% CI: 0.59-2.24 and for women: OR: 1.15; 95% CI: 0.62-2.12]. By BMI status, no significant association was observed between whole day water intake and odds of IBS among normal weight (BMI<25 kg/m2) or overweight and obese people (BMI≥25 kg/m2). CONCLUSION:We found that whole-day water intake was not associated with odds of IBS. A significant association between consumption of >8 glasses of water per day and odds of IBS-M was observed.